Grey seals on the Murman coast, Russia: status and present knowledge - Ziryanov, Sergej V; Mishin, Vasily L (NAMMCO Scientific Publications, 2007)
Grey seals (Halichoerus grypus) are distributed along the entire northern Murman coast in Russia. Breeding sites are located mainly on the Ainov and Seven islands, which belong to the Kandalaksha Nature Reserve. The annual pup production was estimated to be around 800 pups in the early 1990s, and the pup mortality has been observed to be relatively high. The population was estimated to be approximately 3,500 individuals in 1994. Grey seals migrate in small numbers into the White Sea during summer. The grey seal is protected and registered in the Red Books of Russia, Murmansk region and Fennoscandia. The main results of grey seals investigations from 1986 to 2000 are briefly reviewed. There are no recent studies on abundance, seasonal distribution, growth, moulting and feeding of the species.